(untitled) (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2014)
Between 2000 and 2010, the total energy demand for Malaysia has doubled. In order to promote production of renewable energy in Malaysia, the government has introduced a Feed-in Tariff (FiT) scheme under the Renewable Energy Act 2011. This paper examines community readiness towards adopting Building-Integrated Photovoltaic (BIPV) in Raub, Pahang, Malaysia through the FiT scheme. By using the Community Readiness Model proposed by the Tri-Ethnic Center, the analysis shows that the people in Raub are not ready to accept the FiT scheme and to adopt the BIPV system. The main reasons for this are the lack of information about the FiT scheme and high initial installation cost for the BIPV. The study concludes that more measures need to be done to increase community readiness to implement BIPV.